Incidence of Entamoeba Gingivalis and Trichomonas Tenax in Periodontitis and Gingivitis Patients Who Attended to Private Clincs in Babylon Province (Medico Legal Update, 2020)
Trichomonas tenax, a commensal flagellated protozoan, inhabits in human oral cavity. This parasite is cosmopolitan and frequently found in patients with poor oral hygiene and advanced periodontal disease. By using wet mount smear and giemsa staining to detect the prevalence of oral protozoa in patients with oral diseases and a healthy control group. From October 2014 to April 2015, the subgingival dental plaques of 310 patients with gingivitis or periodontitis and 310 controls who attended to clinics periodontics , in Babylon province. 64 (20.6 %) of patients were positive (40.2 % periodontitis ,14.2 % gingivitis) by using wet preparation and Giemsa staining. The prevalence of oral Trichomonas tenax in our study (20.6%) and Entamoeba gingivalis was (42.9 %) was compatible with many other published reports which mostly has ranged from 12%-32%.The study revealed dependence between the frequency of occurrence of protozoa and the state of periodontitis.the age group (41-50)yr. Have high incidence of T.tenax compared with an other groups,as well as the males have high incidence(24.7 %) than females (16.8 %).